LEARNING TREE DIAGRAMS IN SYNTAX: STUDENTS’ DIFFICULTIES AND LEARNING STRATEGIES - Fernando De Napoli Marpaung; Supriadi; Resti Citra Dewi (English Study Program University of Pasir Pengaraian, 2026)
This study examined the difficulties students experience when learning syntactic tree diagrams, the strategies they use to manage these difficulties, their perceptions of the effectiveness of these strategies, and their suggestions for improving instruction. Using a descriptive qualitative design backed by quantitative features, data were collected via a standardized questionnaire from 31 fifth-semester students of the English Education Study Program in Indonesia who had completed a syntax course. The findings show that students primarily struggle with identifying phrase types (Mean: 3.68) and understanding complex sentence structures (Mean: 3.52), as well as applying theoretical concepts to diagram construction (Mean: 3.42). To address these challenges, students rely on a range of strategies, with digital tools—particularly artificial intelligence platforms like ChatGPT and Gemini (Mean: 4.06)—and educational video resources (Mean: 3.74) emerging as the most frequently used and most helpful. While AI provides immediate, step-by-step procedural support, students emphasized that its effectiveness is maximized when combined with collaborative approaches such as peer discussion and direct consultation with lecturers. The study concludes that learning syntactic tree diagrams involves significant conceptual demands, and students benefit most from instructional methods that incorporate visual scaffolding and interactive resources. Future research should employ experimental designs to compare AI-assisted instruction with traditional methods and investigate the impact of digital literacy on students' mastery of syntactic analysis.